"By slapping their laps, the patient will know that you truly care for her": A qualitative study on social norms and acceptability of the mistreatment of women during childbirth in Abuja, Nigeria. (December 2016) - Bohren, Meghan A.; Vogel, Joshua P.; Tunçalp, Özge; Fawole, Bukola; Titiloye, Musibau A.; Olutayo, Akinpelu Olanrewaju; Oyeniran, Agnes A.; Ogunlade, Modupe; Metiboba, Loveth; Osunsan, Olubunmi R.; Idris, Hadiza A.; Alu, Francis E.; et al.
Abstract: Background: Many women experience mistreatment during childbirth in health facilities across the world. However, limited evidence exists on how social norms and attitudes of both women and providers influence mistreatment during childbirth. Contextually-specific evidence is needed to understand how normative factors affect how women are treated. This paper explores the acceptability of four scenarios of mistreatment during childbirth. Methods: Two facilities were identified in Abuja, Nigeria. Qualitative methods (in-depth interviews (IDIs) and focus group discussions (FGDs)) were used with a purposive sample of women, midwives, doctors and administrators. Participants were presented with four scenarios of mistreatment during childbirth: slapping, verbal abuse, refusing to help the woman and physical restraint. Thematic analysis was used to synthesize findings, which were interpreted within the study context and an existing typology of mistreatment during childbirth. Results: Eighty-four IDIs and 4 FGDs are included in this analysis. Participants reported witnessing and experiencing mistreatment during childbirth, including slapping, physical restraint to a delivery bed, shouting, intimidation, and threats of physical abuse or poor health outcomes. Some women and providers considered each of the four scenarios as mistreatment. Others viewed these scenarios as appropriate and acceptable measures to gain compliance from the woman and ensure a good outcome for the baby. Women and providers blamed a woman's "disobedience" and "uncooperativeness" during labor for her experience of mistreatment. Conclusions: Blaming women for mistreatment parallels the intimate partner violence literature, demonstrating how traditional practices and low status of women potentiate gender inequality. These findings can be used to facilitate dialogue in Nigeria by engaging stakeholders to discuss how to challenge these norms and hold providers accountable for their actions. Until women and their families are able to freely condemn poor quality care in facilities and providers are held accountable for their actions, there will be little incentive to foster change. Highlights: Women and providers in Nigeria reported that women experience mistreatment during childbirth. Mistreatment is normalized and accepted for punishing "disobedient" women. Maternity ward power relations between providers and women propagate mistreatment. Mistreatment was acceptable when used by providers to gain compliance and improve health outcomes.